2012
DOI: 10.1021/jf3018113
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on the Use of Visible–Near-Infrared Spectroscopy for the Screening of Individual and Total Glucosinolate Contents in Broccoli

Abstract: 1The potential of visible-near infrared spectroscopy to determine selected individual and 2 total glucosinolates in broccoli has been evaluated. Modified partial least squares 3 (MPLS) regression was used to develop quantitative models in order to predict 4 glucosinolate contents. Both the whole spectrum and different spectral regions were 5 separately evaluated to develop the quantitative models, in all cases the best results were 6 obtained using the NIR zone between 2000 and 2498 nm. These models have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…, Hernández‐Hierro et al. ) and has been applied to several agricultural products and foods (Baye et al. , Gowen et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Hernández‐Hierro et al. ) and has been applied to several agricultural products and foods (Baye et al. , Gowen et al.…”
Section: Introductionmentioning
confidence: 99%
“…The models reported here outperform several others [27][28][29]. The model developed by Chen et al [30] performed better than the present study, and it was useful for qualitative determination of GBS in Chinese kale.…”
Section: Discussionmentioning
confidence: 39%
“…Since humans eat leaf tissue of cabbage and Brussels sprouts rather than the seeds, having quanti cation methods for leaf tissue is more relevant. Six studies have attempted to develop quantitative calibration models for leaf tissue of several GSL-containing plants with various degrees of success [25][26][27][28][29][30], and four of these included GBS for calibration based on dry weight reference values (Table 1). Of those, Sahamishirazi et al [27] reported a model that had poor performance in broccoli orets.…”
Section: Introductionmentioning
confidence: 99%
“…Hernández-Hierro et al [223] examined visible-NIR spectroscopy for freeze-dried broccoli. They concluded that it is potentially usable for screening of almost all individual glucosinolates and total glucosinolates.…”
Section: C1 Class D Type 12: Secondary Food Commodities Ofmentioning
confidence: 99%